Racing the clock : running across a lifetime - Heinrich, Bernd, 1940- (Ecco, an imprint of HarperCollinsPublishers, 2021)
In this part memoir, part scientific investigation, a biologist and natural historian uses his long-distance running to illuminate the changes to a human body over a lifetime, exploring the relationship between metabolism, diet, exercise, and age.